2009
DOI: 10.1136/thx.2008.112136
|View full text |Cite
|
Sign up to set email alerts
|

Early life origins of chronic obstructive pulmonary disease

Abstract: Background: Early life development may influence subsequent respiratory morbidity. The impact of factors determined in childhood on adult lung function, decline in lung function and chronic obstructive pulmonary disease (COPD) was investigated. Methods: European Community Respiratory Health Survey participants aged 20-45 years randomly selected from general populations in 29 centres underwent spirometry in 1991-3 (n = 13 359) and 9 years later (n = 7738). Associations of early life factors with adult forced ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
337
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(367 citation statements)
references
References 49 publications
16
337
0
14
Order By: Relevance
“…[26][27][28][29] Svanes et al observed that childhood risk factors such as maternal smoking, childhood respiratory infections, and childhood asthma were strongly related to the development of COPD in young adults. 30 Nevertheless, although our results highlight the important role of maximally attained lung function in early adulthood, Shown is the distribution of observed annual decline in forced expiratory volume in 1 second (FEV 1 ) among 2864 participants in the Framingham Offspring Cohort (FOC) and the Copenhagen City Heart Study (CCHS), according to the four trajectories defined on the basis of a normal FEV 1 (≥80% of the predicted value) or low FEV 1 (<80% of the predicted value) at baseline and the presence or absence of chronic obstructive pulmonary disease (COPD) at the final examination. Participants were considered to have COPD if they had grade 2 or higher COPD according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 1 grading system; grade 2 or higher COPD according to GOLD is defined as a ratio of FEV 1 to forced vital capacity of less than 0.70 and an FEV 1 of less than 80% of the predicted value, with the use of the prediction equations from the National Health and Nutrition Examination Survey for the FOC and local prediction equations for the CCHS.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Svanes et al observed that childhood risk factors such as maternal smoking, childhood respiratory infections, and childhood asthma were strongly related to the development of COPD in young adults. 30 Nevertheless, although our results highlight the important role of maximally attained lung function in early adulthood, Shown is the distribution of observed annual decline in forced expiratory volume in 1 second (FEV 1 ) among 2864 participants in the Framingham Offspring Cohort (FOC) and the Copenhagen City Heart Study (CCHS), according to the four trajectories defined on the basis of a normal FEV 1 (≥80% of the predicted value) or low FEV 1 (<80% of the predicted value) at baseline and the presence or absence of chronic obstructive pulmonary disease (COPD) at the final examination. Participants were considered to have COPD if they had grade 2 or higher COPD according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 1 grading system; grade 2 or higher COPD according to GOLD is defined as a ratio of FEV 1 to forced vital capacity of less than 0.70 and an FEV 1 of less than 80% of the predicted value, with the use of the prediction equations from the National Health and Nutrition Examination Survey for the FOC and local prediction equations for the CCHS.…”
Section: Discussionmentioning
confidence: 99%
“…The early life factors that have been implicated in poor future lung health include environmental tobacco smoke, antenatal nutrition, premature birth, respiratory infections in early life, air pollution, social deprivation, obesity and asthma. [5][6][7][8] To reduce the global burden of respiratory disease we should target modifiable early life factors known to be associated with subsequent respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that an early-life history of respiratory disease increases the mortality caused by COPD. 2,9 Especially the occurrence of transient early wheeze (TEW) in childhood can constitute a first sign of disturbed early lung development and lung growth because TEW has been shown to associate with reduced lung function already soon after birth, which is probably caused by genetic constitution, in utero exposures (eg, cigarette smoke), or both. 10 Furthermore, these airway developmental abnormalities related to TEW have been shown to associate with lower lung function when symptoms have disappeared, which then persists through the rest of childhood and adolescence.…”
mentioning
confidence: 99%